Burnout and Cognitive Functioning: Are We Underestimating the Role of Visuospatial Functions? - Koutsimani, Panagiota; Montgomery, Anthony (Frontiers in Psychiatry, 2022)
Job burnout is a psychological syndrome which results from chronic occupational stress and cognitive impairments are among its negative consequences. The demands of the COVID-19 pandemic have challenged the healthcare system increasing the risk of job burnout among healthcare professionals. The studies conducted so far have mainly focused on the effects of job burnout on executive functions. Visuospatial functions are a cognitive domain which plays an important role in healthcare workers' optimal performance. Healthcare workers are constantly relying on their visuospatial abilities in order to care for their patients as they are required to use techniques that involve manipulation of medical instruments, they need to have excellent hand-eye coordination and great perception of spatial anatomy, factors that can affect healthcare workers' performance is of significance and can put patient safety at risk. However, our understanding of how visuospatial functions are being affected in job burnout is limited. The scope of this mini-review is to examine the evidence concerning the relationship of job burnout with visuospatial functions. The sparsity of the relevant empirical evidence does not allow for definite conclusions. However, given the implications of diminished visuospatial abilities in patient safety we highlight the need for studies exploring the effects of job burnout on visuospatial functions. Limitations of studies are discussed.